Evaluating subjective cognitive decline: a systematic review of tools available for evaluating cognitive complaints in Portuguese - Wyllians Vendramini BORELLI; Vanessa Nicola LABREA; Eduardo LEAL-CONCEICAO; Mirna Wetters PORTUGUEZ; Jaderson Costa da COSTA (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Subjective cognitive decline (SCD) is a perception that is not objectively measured in screening tests. Although many tools are available for evaluating SCD, no single gold standard is available for classifying individuals as presenting SCD, in the Portuguese-speaking population. The aim of this study was to systematically review the literature for tools used to evaluate SCD in the Portuguese-speaking population. Methods: Four databases (Web of Science, SciELO, LILACS and MEDLINE) were primarily utilized in this study (Phase 1). Subsequently, we conducted a manual search of the literature (Phase 2). We then retrieved tools for critical evaluation (Phase 3). Studies that matched the inclusion criteria were analyzed. We summarized the features of each tool in terms of the number of questions, scoring system, benefits and deficiencies, translation and validity. Results: A total of 30 studies utilizing four questionnaires and seven different single questions were found. The tools retrieved were the Memory Assessment Questionnaire (MAC-Q; 12/30 studies), single-question methods (7/30 studies), Subjective Memory Complaint Scale (SMC scale; 5/30 studies), Prospective and Retrospective Memory Questionnaire (PRMQ; 3/30 studies) and Memory Complaint Scale (MCS; 3/30 studies). Only two were formally translated and validated for the Portuguese speaking population (PRMQ and MCS). Conclusions: In summary, SCD is still underinvestigated in Portuguese-speaking countries. The MAC-Q was the most commonly used tool in Portuguese, despite its lack of formal translation and validation for the Portuguese-speaking population. Further studies are required in order to develop and validate a screening tool that includes questions for detecting SCD-plus features and affective symptoms, so as to improve its predictive value.